Neck Circumference Predicts Mortality in Hospitalized COVID-19 Patients - Stefano Di Bella; Verena Zerbato; Gianfranco Sanson; Erik Roman-Pognuz; Paolo De Cristofaro; Andrea Palermo; Michael Valentini; Ylenia Gobbo; Anna Wladyslawa Jaracz; Elizabeta Bozic Hrzica; Cristiane Campello Bresani-Salvi; Alexandre Bezerra Galindo; et al. (MDPI AG, 2021)
We aimed to determine whether neck circumference predicts mortality among hospitalized COVID-19 patients with respiratory failure. We performed a prospective multicenter (Italy and Brasil) study carried out from March to December 2020 on 440 hospitalized COVID-19 patients with respiratory failure. Baseline neck circumference was measured. The study outcome was 30- and 60-days mortality. Female and male participants were classified as "large neck" when exceeding fourth-quartile. Patients had a median age of 65 years (IQR 54-76), 68% were male. One-quarter of patients presented with grade-1 or higher obesity. The median neck circumference was 40 cm (IQR 38-43): 38 cm (IQR 36-40) for female and 41 cm (IQR 39-44) for male subjects. "Large neck" patients had a significantly higher prevalence of hypertension (63 vs. 48%), diabetes (33 vs. 19%), obesity (26 vs. 14%), and elevated C-reactive protein (CRP) (98 vs. 88%). The cumulative mortality rate was 13.1% (n = 52) and 15.9% (n = 63) at 30 and 60 days, respectively. After adjusting for age, BMI, relevant comorbidities, and high C-reactive protein to albumin ratio, "large neck" patients showed a significantly increased risk of death at 30- (adjusted HR 2.50; 95% CI 1.18-5.29; p = 0.017) and 60-days (adjusted HR 2.26; 95% CI 1.14-4.46; p = 0.019). Neck circumference is easy to collect and provides additional prognostic information to BMI. Among hospitalized COVID-19 patients with respiratory failure, those with large neck phenotype had a more than double risk of death at 30 and 60 days.